FAKTOR YANG BERHUBUNGAN DENGAN KADAR CHOLINESTERASE DARAH PEKERJA BAGIAN PENYEMPROTAN PT. ANGLO EASTERN PLANTIONS - Dian Maya Sari Siregar (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2021)
ABSTRACT The spraying process is a condition where workers are very likely to be exposed to toxic chemicals contained in pesticides. Problems encountered in the field, workers do not spray with the correct method and do not use a complete PPE. The danger that can occur when spraying is a disturbance in the enzyme Cholinesterase (CHE) in the blood. CHE is an enzyme that is in the body's tissues has a role to keep nerve cells, muscles and glands working properly. The purpose of this study was to determine the factors related to CHE levels in spraying workers. The research design used analytical research with cross sectional approach. The population was 30 spraying workers. The sampling technique used a total population of 30 people. Data analysis used univariate and bivariate analysis tested by Fisher Exact Test statistical test. Data obtained by questionnaire and examination of CHE levels through blood samples. The results with bivariate analysis revealed p-value of each variable, namely age .143>.05, gender 1,000>.05, education level .374>.05, years of service .071>.05, duration of exposure .02<.05, spraying method 0,000<.05, the last spraying time was .210>.05 and PPE .001 <.05. The conclusion shows that there is a relationship between the length of exposure to pesticides, how to spray and PPE with CHE levels. Keywords: Related Factors, Cholinesterase Levels, Spraying Workers